Supplements and high-protein foods in weight training: How do they affect maximum muscle strength? - Adnan Fardi; Tjung Hauw Sin; Angga Okta Pratama; Deby Tri Mario (UIR Press, 2022)
Consumption of protein in weight training when adjusted to the needs will result in perfect muscle growth and development, especially in increasing maximum strength. In fact, many Fitness Members consume protein without paying attention to the dose, so that increasing maximum strength is not realized properly. This study aims to provide high-protein supplements and high-protein foods in weight training to increase maximum muscle strength. The design used in this study is a three group pre test and post test, consisting of a group consuming high protein supplements, a group consuming a high protein diet and a control group. The population in this study are FIK UNP students, with a total sample of 39 people. The instrument used in this study is a maximum strength test (leg & Hand Dynamo Meter test). The data obtained in this study are analyzed by analysis of variance (ANOVA) with = 0.05. The results showed: (1) There was a difference in effect between the group given high protein supplements, high protein die,t and the control group, (2) The group given high protein supplements had a difference from the average of the other two groups, (3) The group given high protein supplements high-protein supplements had a difference from the average of the other two groups, (4) The high-protein diet group did not have a mean difference with the control group. The limitation in this study is that the researcher was not able to control aspects that were outside the research activities such as other high protein contamination consumed by the research food samples. The next stage, this research will look at the effects of consuming high-protein supplements on a sustainable basis on human health.